Perpetual debt valuation: the net present value myopia - Reis, Pedro (2017)
Would you prefer to receive a fixed rent for a period of 50 years, 75 years or perpetually? Well, if you have chosen the perpetual option, you are absolutely right. However, when considering a mathematical and financial approach, they may all end up roughly the same whenever the Net Present Value (NPV) is approximately identical. It makes common sense to choose the perpetual option even if the NPV exhibits myopia when computing the discount value of a fixed yearly rent. After a certain period, the discount value becomes approximately the same even when adding more yearly fixed rents. Corporations and governments issue perpetual bonds while recognizing these may not represent a very good financing strategy and thus implying that most of these issues are either callable or convertible on the issuer’s request. In approaching the existing perpetual debt related NPV myopia, this paper holds two main goals: firstly, we intend to study the behaviours of perpetual debt yields against other perpetual instruments and, secondly, we consider the financial methods for assessing the value of money before proposing a formula adjustment that might serve to overcome default NPV when evaluating fixed rents in perpetuity.